The potential efficacy of continuous plantar foot cooling during relatively mild simulated occupational heat stress—a pilot study - Jason M. Keeler; Charlie Walker; Amanda Regester; Molly Heikkinen; Blair D. Johnson; Y. Sungtaek Ju; Lihua Jin; Zachary J. Schlader (European Journal of Applied Physiology, 2026)
Purpose To identify the effect size regarding glabrous skin foot cooling on core temperature, cognitive performance, and physical work capacity (PWC) during mild simulated occupational heat stress. Methods A pilot sample of twelve healthy adults (5 women) completed experimental visits in a 38.7 ± 0.7 ℃ and 46 ± 9% relative humidity environment that consisted of 60-minutes of steady-state upper body ergometry exercise followed by a 60-minute PWC test involving upper body ergometry while maintaining a rating of perceived exertion of 13 (“somewhat hard”). In one trial, participants stood with bare feet on cooled plates (17.7 ± 0.5 ℃) and in the other they were on noncooled plates (36.5 ± 0.1 ℃), with the order assigned in a block randomized manner. Results Core temperature increased during steady-state exercise (from 37.5 ± 0.3 to 37.6 ± 0.3 ℃, p < 0.003) and the PWC test (from 37.6 ± 0.3 to 37.9 ± 0.3 ℃, p < 0.001), but there was no difference between conditions (mean difference 0.03±0.18 ℃, p ≥ 0.592, d z =0.112). During the PWC test, there was no difference between conditions for mean power output ( p = 0.213, d z =0.184), with the final power outputs of 28 ± 9 W and 30 ± 9 W for control and cooling conditions, respectively. There were no condition effects for cognitive performance on any measure ( p ≥ 0.207, d z ≤0.405). However, foot cooling (+ 15 ± 9 bpm) reduced increases of heart rate during the PWC test compared to control (+ 21 ± 11 bpm, p = 0.013, d z =0.425). Conclusion Glabrous skin foot cooling has a relatively small effect on core temperature and PWC, but moderate effects on cognitive performance and heart rate during short duration (~ 3 h) mild heat stress.